Egg essentials - Abdul Karim, Muhammad Shahrim; Mohd Ghazali, Hasanah; Abu Bakar , Ainul Zakiah (Universiti Putra Malaysia Press, 2015)
Eggs are symbol of fertility. For generations eggs have been used as protein that is required by our bodily functions. Not only fresh eggs are used, many preserved eggs are also popular in many countries. For the Malays, hard boiled eggs are used as gifts in many events, especially in wedding reception and thanksgiving ceremonies. Telur pindang, which is popular in the state of Johor, is a hard boiled herbal egg that is served at weddings. It has been adopted from the Chinese culture. However, in the Chinese culture, century eggs and salted duck eggs have been passed down for many generations.